2000
DOI: 10.1097/00007890-200001270-00013
|View full text |Cite
|
Sign up to set email alerts
|

LIVER ALLOTRANSPLANTATION AFTER EXTRACORPOREAL HEPATIC SUPPORT WITH TRANSGENIC (hCD55/hCD59) PORCINE LIVERS

Abstract: The CD55/CD59 transgenic porcine liver appears capable of safely "bridging" a patient to liver transplantation. Human PoERV infection from these livers has yet to be demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
4

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(23 citation statements)
references
References 19 publications
0
19
0
4
Order By: Relevance
“…Also, the antibodies used for Western blotting should be antihuman rather than (in the majority) anti-rat or rabbit, as it has been used in works of Friis (1999, 2000) or in our article on this subject Hence, the article by Myers et al (2001) opens some interesting questions and contributes to the general knowledge of the pig (minipig) liver microsomal P450 enzymes. Because the (mini)pig is a purported source of cells, tissues, and organs in human therapy (see Levy et al, 2000 or Dixit and Gitnick, 1996 for a review) and, possibly, a species of choice for studies of hepatic metabolism of drugs in humans , these studies are needed. …”
mentioning
confidence: 99%
“…Also, the antibodies used for Western blotting should be antihuman rather than (in the majority) anti-rat or rabbit, as it has been used in works of Friis (1999, 2000) or in our article on this subject Hence, the article by Myers et al (2001) opens some interesting questions and contributes to the general knowledge of the pig (minipig) liver microsomal P450 enzymes. Because the (mini)pig is a purported source of cells, tissues, and organs in human therapy (see Levy et al, 2000 or Dixit and Gitnick, 1996 for a review) and, possibly, a species of choice for studies of hepatic metabolism of drugs in humans , these studies are needed. …”
mentioning
confidence: 99%
“…Immunoapheresis has been demonstrated to delay HXR and thus to improve perfusion (6). Just recently, Levy et al reported two patients with liver failure that were bridged to transplantation by ECLP with transgeneic organs (15). In all these cases, however, it still remains speculative whether long-term ECLP is beneficial or even harmful for the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Two of these patients are alive today for more than 28 years later, and are in excellent health [59][60][61]. Other investigators have used similar apparatus using the livers from transgenic pigs to keep these patients alive until a human liver becomes available for transplantation [62].…”
Section: The Use Of Animal Organs and Xenotransplantationsmentioning
confidence: 99%